Corporate Social Responsibilty Tambang Batubara dan Pengaruhnya terhadap Kesejahteraan Masyarakat di Kabupaten Kutai Timur - Habibah, Nur; Tampubolon, Frances Roi Seston (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) by PT Pamapersada Nusantara in East Kutai Regency and its impact on community welfare. Quantitative research methods were used by using survey data from communities around the mine and company employees. The results of descriptive and regression statistical analysis showed a significant relationship between the CSR program and community welfare. Most respondents had a high awareness of CSR programs and positive perceptions of their benefits, especially in improving social infrastructure, education, health, and the environment. Regression analysis shows that CSR programs have a significant impact on the welfare of communities around mines, with a coefficient of determination of 0.555. The implication of these findings is the importance of integrating holistic and sustainable CSR practices into companies business strategies in order to improve welfare and support sustainable development in their areas of operation.